Efektivitas Media Pembelajaran Memrise Dalam Pembelajaran Maharah Kitabah Bahasa Arab MTs Al-Hidayah Batu - Mujib, Ahmad; Saleha, Ela; Maksum, M. Syukron; Santosa, Afriana (AL-MUTSLA, 2025)
This research aims to describe the effectiveness of Memrise learning media in learning Maharah Kitabah Arabic at MTs Al-Hidayah Batu. This is based on technological developments. To achieve the goal, the author uses quantitative research methods with experimental design. The research subjects in this study were class IX students of MTS SA AL-HIDAYAH Batu City. The population in this study was class IX students at MTS SA AL-HIDAYAH, Batu City, totaling 22 students. The instrument used is a test. Data resulting from statistical analysis used the t-test to determine the significance of the difference in pre-test and post-test averages. The results of the research show that the effectiveness of Memrise learning media is in increasing the ability to understand the Arabic book of MTs Al-Hidayah Batu. Based on the T test of 0.9781 > 0.05, it can be concluded that there is a significant difference between Increasing the Ability to Maharah Kitabah and the use of conventional media. Apart from that, the average difference between the pretest and posttest in the experimental class was 31.3636. Meanwhile, the average difference between the pretest and posttest in the control class was 36.8182. This indicates that the use of memrise learning media is an effective alternative for improving the ability to understand the Book of the Bible.